Learners in a Changing Learning Landscape
XII, 302 p.
Keywords: This book is about questions. Today's learners face constant change. Adaptive learner expertise is key to their survival on a learning journey that lasts a lifetime. This requires new thinking of all actors in the learning environment. The fundamental process through which this book was created is an extended in-depth dialogue among researchers, lifelong learners, educators, and thinkers. "Working on this book was a very special kind of experience," says John Bransford (University of Washington), a contributing author to the book and renowned researcher on how people learn. While participating in the dialogue "we were all helped to ‘walk our talk’ and use technology to improve everything we did… I'm convinced that the conversations will not end with this book. Through technology-based dialogue facilitated by the magic touch of the editors’ leadership, I'm sure that all of us—authors and readers of this volume—will continue to learn from one another. This is the way that collaborative science should work.".